Analysis of Digitalization Strategy Implementation for Insurance Service Sustainability (Case Study on XYZ Insurance Company) - Sabarini, Nur Endah; Mukti, Aloysius Harry (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
Digital transformation has become a strategic imperative for insurance companies to remain competitive amidst growing industry challenges and evolving customer preferences. XYZ Insurance Company faces obstacles in integrating digital technologies into its operations, including limited infrastructure, organizational resistance, and heightened cybersecurity risks. However, opportunities such as increasing demand for digital services and supportive government regulations present avenues for enhancing competitiveness. This study aims to analyze the implementation of digitalization strategies at XYZ Insurance Company through the SWOT framework, identifying strengths, weaknesses, opportunities, and threats. Using a qualitative case study approach, data were collected through in-depth interviews, direct observations, and company document analysis. The findings reveal that the company benefits from strong market reputation and customer loyalty but struggles with inadequate employee training and underdeveloped technological infrastructure. Key opportunities stem from emerging technologies and favorable regulations, while the main threats include competition from insurtech firms and data security concerns. Strategic recommendations include investing in robust technological infrastructure, strengthening cybersecurity measures, and developing employee capabilities to adapt to digital advancements, ensuring business sustainability in an increasingly competitive landscape.